2010
DOI: 10.1136/thx.2010.153114
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis, non-invasive ventilation and mortality in hospitalised COPD exacerbations

Abstract: Background Reports of non-invasive ventilation (NIV) use in clinical practice reveal higher mortality rates than in corresponding randomised clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
153
3
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 19 publications
14
153
3
10
Order By: Relevance
“…National COPD audits from the UK and Spain [13,14] have reported similar proportions of respiratory acidosis, and this European audit confirms the previous findings. Respiratory acidosis, when split into severe ( pH <7.25) and mild ( pH 7.25-7.35) as a surrogate of the severity of the exacerbation, was a strong predictor of in-hospital and post-discharge mortality.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…National COPD audits from the UK and Spain [13,14] have reported similar proportions of respiratory acidosis, and this European audit confirms the previous findings. Respiratory acidosis, when split into severe ( pH <7.25) and mild ( pH 7.25-7.35) as a surrogate of the severity of the exacerbation, was a strong predictor of in-hospital and post-discharge mortality.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the number of intubated patients after NIV failure was very small, indicating that NIV was a ceiling therapy for most of the cases who died after NIV. Reasons for delaying or withholding NIV are dependent on physicians' decisions, but may also be influenced by the availability of NIV and access to the intensive care unit (ICU) for COPD patients, as first reported by ROBERTS et al [14] and confirmed by this European COPD Audit [9]. This is alarming when guidelines recommend that NIV should be delivered in a dedicated setting and ICU admission should be considered in respiratory failure for COPD [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent UK audit demonstrated that patients with AE-COPD are receiving NIV in the presence of mixed metabolic and respiratory acidosis (although acidotic hypercapnia was not described), and those with bicarbonate below 23 mmol/L have a higher mortality than those with normal/high bicarbonate [6]. However, at present, there are insufficient data to suggest whether and how long NIV should be used in these circumstances.…”
Section: Discussionmentioning
confidence: 90%
“…On the contrary, EDs were less preferred by the physicians compared to prior surveys (13,16). We can increase the awareness, availability and frequency of NIV use in EDs by providing equipment and training courses emphasizing the importance of not delaying NIV for transfer of sicker patients, with the possibility of increased mortality otherwise (33)(34)(35). Although very infrequent, the restriction of NIV use for IMCU and/or ICU was more prominent for specialists from non-teaching hospitals.…”
Section: Discussionmentioning
confidence: 99%